TEXT MINING FACTORS INFLUENCING CONSUMER INTENTION TO USE ROBLOX METAVERSE PLATFORM FROM CUSTOMER REVIEWS - Mario Putra Yuda; Adi Setiawan (JEA17: Jurnal Ekonomi Akuntansi, 2026)
The development of metaverse platforms, which are interactive virtual worlds that integrate entertainment, social interaction, and digital economic activity, has been aided by the quick development of digital technology. One of the most well-known metaverse platforms is Roblox, which gives users the chance to communicate, produce content, and take part in a variety of virtual events. This study looks into how consumer intention and reviews are impacted by the Roblox Metaverse Platform. It also examines how the relationship between the platform and customer feedback is mediated by consumer intention. This study employs an explanatory quantitative methodology, gathering data from active Roblox users via online surveys. The sample technique utilized is called snowball sampling, and the data is examined to find correlations between the variables using path analysis. The findings demonstrate that the Roblox Metaverse Platform has a favorable and significant impact on customer reviews as well as consumer intention. Furthermore, client Intention has a favorable and noteworthy influence on Customer Reviews and acts as a mediating variable that links the platform experience to client assessments. Overall, the findings show how crucial user experience is to promoting sustained use and fostering favorable opinions about metaverse platforms. These results imply that enhancing user intention and customer feedback can be achieved by boosting platform quality and interaction features. Keywords: Metaverse, Roblox, Technology Acceptance Model, Consumer Intention, Customer Reviews